High speed end milling of a zirconium alloy. Issue 1 (2015) - Hood, Richard; Soo, Sein Leung; Sage, Colin; Carcass, Phill
Abstract: The paper details a comprehensive investigation into the machinability and surface integrity of Zircaloy-4 following end milling. Tool wear after machining for ∼30 min at a cutting speed of 320 m/min was low, with surface roughness (Ra) values typically <0.6 μm. No evidence of thermal damage was detected on any of the surface/subsurface cross-sections analysed, although adhesion/re-deposition and smeared material with a width of ∼50 μm was prevalent on the workpiece surface, particularly when operating at higher cutting speeds (320 m/min) and depths of cut (0.6 mm). Surface residual stresses were compressive up to a value of 120 MPa.